2021
DOI: 10.21037/atm-21-726
|View full text |Cite
|
Sign up to set email alerts
|

Research hotspots and trends of microRNA in periodontology and dental implantology: a bibliometric analysis

Abstract: Background: Periodontal disease is a leading cause of tooth loss, and microRNA (miRNA) has been shown to regulate various biological processes. This study aimed to quantitatively analyze the literature related to miRNA in periodontology and dental implantology and summarize the research hotspots and trends in this field.Methods: Literature records from 1985 to 2020 were obtained from the Web of Science Core Collection database. After manual selection, the data was used for cooperative network analysis, keyword… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 60 publications
(55 reference statements)
0
9
0
Order By: Relevance
“…It can systematically visualize the development of the research topics and show the current trends and hotspots of a certain field. Moreover, it has been widely used across many research fields ( 17 ). Citespace software ( 18 ), VOSviewer (visualizations of similarities, van Eck and Waltman, Leiden University, Leiden, Netherlands) ( 19 ) software, and the Online Analysis Platform of Literature Metrology ( ) can be used for detailed analysis of countries/regions, institutions, journals, authors, co-citations and keywords of a certain field.…”
Section: Introductionmentioning
confidence: 99%
“…It can systematically visualize the development of the research topics and show the current trends and hotspots of a certain field. Moreover, it has been widely used across many research fields ( 17 ). Citespace software ( 18 ), VOSviewer (visualizations of similarities, van Eck and Waltman, Leiden University, Leiden, Netherlands) ( 19 ) software, and the Online Analysis Platform of Literature Metrology ( ) can be used for detailed analysis of countries/regions, institutions, journals, authors, co-citations and keywords of a certain field.…”
Section: Introductionmentioning
confidence: 99%
“…Vosviewer identifies each of the clusters in the literature network by selecting sample phrases from the cited literature. By analyzing the citation network and keywords in the time dimension to discover the development, flourishing, and collapse of certain research clusters, we may detect the research hotspots and trends of a given era (Gao et al, 2021). According to our findings, the difference between coauthorship and citation figures showed that this subject is a global concern and needs to much more international collaboration studies (co-authorship).…”
Section: Black Sea Journal Of Health Sciencementioning
confidence: 75%
“…According to Table S1, the total number of publications in the USA (87,065) was greater than that in China (65,250) and far greater than that in France (13,809), Canada (13,496), and the other top 10 most cited countries. The total citations of the United States and China are far more than the other top 10 most cited country citations combined.…”
Section: Global Trends In Effects Of Intestinal Microbes On Obesitymentioning
confidence: 99%
“…China ranked first with 3036 publications, accounting for 34.16% of all publications, followed by the United States (2356, 26.51%) and Spain (480, 5.40%) (Table 1, Figure 2a). Nevertheless, the United States tops the ranking of the most cited countries with a frequency (number of documents) of 87,065, followed by China (65,250), France (13,809), and Canada (13,496) (Table S1). The country collaboration map shows the overall perspective of country and region academic cooperation (Figure S1).…”
Section: Distribution and Cooperation Between Countries/regions And I...mentioning
confidence: 99%